The design and application of a drainage bag with flushing function (一种具备冲洗功能的引流袋的设计与应用) - WANG Meiying (王美英); LI Ying (李颖) (中西医结合护理)
Drainage techniques play an important role in ensuring the recovery safety of patients and prevent complications. Drainage bags have been widely applied in various clinical scenarios such as postoperative drainage of thoracic cavity, abdominal cavity, etc. With the continuous improvement of medical standards, patients' demands for the safety, convenience and comfort of using nursing equipment are also increasing day by day. This paper introduced a utility model, through the set flow control component, quantitative drainage component, automatic liquid discharge component and fixed component, can realize the automatic quantitative discharge of the liquid in the drainage bag, without the need for medical staff to monitor throughout the process, reducing the work intensity of medical staff, and also meeting the usage requirements of patients. (引流技术在临床护理中具有重要地位, 是保障患者恢复安全和预防并发症的重要手段。引流袋作为一种常用的辅助设备, 广泛应用于手术后、胸腔、腹腔等多种临床场景。随着医疗水平的不断提升, 患者对护理设备的安全性、便捷性与舒适度提出了更高要求。本研究设计一种新型引流袋, 通过其流量调控组件、定量引流组件、自动排液组件和固定组件的创新设置, 实现了引流袋内液体的自动定量排放。该设计无需医护人员全程监护, 有效降低了医护人员的工作强度, 同时满足了患者的使用需求, 对提高护理质量和患者满意度有着积极作用。)